A One-Year Economic Evaluation of Six Alternative Strategies for the Management of Uninvestigated Upper Gastrointestinal Symptoms in Canadian Primary Care - Alan N Barkun; Ralph Crott; Carlo A Fallone; Wendy A Kennedy; Jean Lachaine; Carey Levinton; David Armstrong; Naoki Chiba; Alan Thomson; Sander Veldhuyzen van Zanten; Paul Sinclair; Sergio Escobedo; et al. (Canadian Journal of Gastroenterology)
BACKGROUND: The cost-effectiveness of initial strategies in managing Canadian patients with uninvestigated upper gastrointestinal symptoms remains controversial.